The Effectiveness of The Picture and Picture Learning Model in Improving Student Learning Outcomes In Elementary Schools - Yuslia, Defi; Hasnah, Hasnah; Safarudin, Rizal; Helfikri, Helfikri (Khalifa Journal of Islamic Education, 2021)
This study aims to analyze the effectiveness of the picture and picture learning model on learning outcomes of Islamic education in elementary schools. The experimental research was conducted through the Classroom Action Research (CAR) method. The research subjects were twenty-seven elementary school students consisting of fifteen male students and twelve female students. Research data were collected through the researcher's daily notes of all students, observations, interviews, and learning test results of two learning cycles. All data were analyzed descriptively using the Statistical Program for Social Science (SPSS) software version 20. Overall, the results showed that the implementation of the picture and picture learning model in Islamic education was effective in improving student learning outcomes. After the picture and picture learning was practiced, the completeness and improvement of students’ final scores are above the Minimum Completeness Criteria (KKM) with an increase of 29.63% in the first cycle and 85.19% in the second cycle. Referring to the results, the picture and picture is one of the alternative learning models that can be implemented by teachers to improve student learning outcomes in Islamic education.